Differences in Social Loafing Among Guidance and Counseling Students Based on University Cohort - Elvira Linanda Putri; Rezki Hariko (Scidacplus, 2026)
Social loafing, the tendency of individuals to exert less effort in groups than independently, poses a significant challenge to collaborative learning in higher education. This study aimed to analyze and compare the levels of social loafing among Guidance and Counseling students at Universitas Negeri Padang based on their academic cohort (2024 and 2025). Utilizing a quantitative descriptive-comparative design, data were collected from 135 participants (66 from the 2024 cohort and 69 from the 2025 cohort) using a Social Loafing Scale based on Myers' theory. Data were analyzed using descriptive statistics and an independent samples t-test. The findings revealed that students' social loafing levels generally fell within the moderate category (M = 17.727, SD = 2.763). Descriptively, both cohorts exhibited low levels of social loafing; however, the 2024 cohort showed a significantly higher mean score (M = 107.39, SD = 15.055) than the 2025 cohort (M = 89.67, SD = 16.942). An independent samples t-test indicated that this difference was statistically significant, t(df) = 133, p < 0.05 (or p = .000). Responsibility diffusion was most prominent in the 2024 cohort, while passive attitudes characterized the 2025 cohort. These results suggest that academic seniority and group-work experience influence social loafing behavior. Consequently, lecturers and counselors should implement agentic guidance models and collaborative strategies to foster individual accountability and minimize social loafing in academic settings.